2022
DOI: 10.1101/2022.07.15.500059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multi-Tissue Comparison and Molecular Characterization of Canine Organoids

Abstract: Organoids are 3-dimensional (3D) stem cell-derived cell culture lines that offer a variety of technical advantages compared to traditional 2-dimensional (2D) cell cultures. Although murine models have proved useful in biomedical research, rodent models often fail to adequately mimic human physiology and disease progression, resulting in poor preclinical prediction of therapeutic drug efficacy and toxicity. With the advent of organoid technology, many of these challenges can be overcome. Previously, the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…The isolation process for other tissues have been similar with possible other markers used to detect stem cells (e.g., EpCAM for liver) [35]. Additionally, Zdyrski et al reported the isolation of various canine tissues using identical procedures leading to standardization of these techniques [36].…”
Section: Stem Cell-derived Organoidsmentioning
confidence: 99%
“…The isolation process for other tissues have been similar with possible other markers used to detect stem cells (e.g., EpCAM for liver) [35]. Additionally, Zdyrski et al reported the isolation of various canine tissues using identical procedures leading to standardization of these techniques [36].…”
Section: Stem Cell-derived Organoidsmentioning
confidence: 99%
“…The structural integrity of the cell monolayer was monitored every other day for up to two weeks by phase-contrast microscopy. Colonoid-derived monolayers and colonoids were fixed and processed for histology and/or TEM, as described in prior studies [35,36,60].…”
Section: Preparation Of 2d Canine Colonic Monolayer and Maintenancementioning
confidence: 99%
“…HBSS buffer with pH 7.4 was added to the BL chambers. At pre-defined time points (15,30,45,60,90, and 120 min), samples of 100 µL buffer were collected from the receiver chamber (BL) and replaced with the same volume (i.e., 100 µL) of transport buffer at pH 7.4. For the AP side, drug concentrations of the donor solution were measured prior to introduction into the well and at the end of the study (120 min).…”
Section: Apical-to-basolateral (Ap→bl) Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation